The effect on consent rates for deceased organ donation in Wales after the introduction of an opt‐out system. (5th May 2020) - Madden, S.; Collett, D.; Walton, P.; Empson, K.; Forsythe, J.; Ingham, A.; Morgan, K.; Murphy, P.; Neuberger, J.; Gardiner, D.
Summary: Organ transplantation saves and transforms lives. Failure to secure consent for organ retrieval is widely regarded as the single most important obstacle to transplantation. A soft opt‐out system of consent for deceased organ donation was introduced into Wales in December 2015, whilst England maintained the existing opt‐in system. Cumulative data on consent rates in Wales were compared with those in England, using a two‐sided sequential procedure that was powered to detect an absolute difference in consent rates between England and Wales of 10%. Supplementary risk‐adjusted logistic regression analysis examined whether any difference in consent rates between the two nations could be attributed to variations in factors known to influence UK consent rates. Between 1 January 2016 and 31 December 2018, 8192 families of eligible donors in England and 474 in Wales were approached regarding organ donation, with overall consent rates of 65% and 68%, respectively. There was a steady upward trend in the proportion of families consenting to donation after brain death in Wales as compared with England and after 33 months, this reached statistical significance. No evidence of any change in the donation after circulatory death consent rate was observed. Risk‐adjusted logistic regression analysis revealed that by the end of the study period the probability of consent to organ donation in Wales was higher than in England (OR [95%CI] 2.1 [1.26–3.41]). The introduction of a soft opt‐out system of consent in Wales significantly increased organ donation consent though the impact was not immediate.